Corneaulcus på häst - Andersson, Daniela (2018)
Corneal ulcer is frequently diagnosed in horses. Horses seem more prone to complications such as infections and keratomalacia compared to other domestic animals (Ollivier, 2005). Early diagnosis as well as prompt and adequate treatment is essential for the ulcer to heal without complications. Cytology and microbial culture are the diagnostic tests of choice and although microbial culture is regarded golden standard, cytology can generate quick and additional information (Hindley et al., 2016; Keller & Hendrix, 2005; Massa et al., 1999; McLeod et al., 1996). Cytology can, for example, give information about the presence of neutrophils, a cell that frequently contribute to the complicating keratomalacia, and additionally also detect fungus and other inflammatory cells such as eosinophils (Gilger, 2017; Matsumoto et al., 1993; Ollivier, 2005).